A study of local turbulence and anisotropy during the afternoon and evening transition with an unmanned aerial system and mesoscale simulation - A. Lampert; F. Pätzold; M. A. Jiménez; L. Lobitz; S. Martin; G. Lohmann; G. Canut; D. Legain; J. Bange; D. Martínez-Villagrasa; J. Cuxart (Atmospheric Chemistry and Physics, 2016)
Observations of turbulence are analysed for the afternoon and evening transition (AET) during the Boundary-Layer Late Afternoon and Sunset Turbulence (BLLAST) experimental field campaign that took place in Lannemezan (foothills of the Pyrenees) in summer 2011. The case of 2 July is further studied because the turbulence properties of the lower atmosphere (up to 300 m above ground level) were sampled with the Meteorological Mini Aerial Vehicle (M2AV) from turbulently mixed to stably stratified atmospheric conditions. Additionally, data from radiosoundings, 60 m tower and UHF wind profiler were taken together with the model results from a high-resolution mesoscale simulation of this case. Weak large-scale winds and clear-sky conditions were present on the studied AET case favouring the development of slope winds and mountain–plain circulations. It is found that during the AET the anisotropy of the turbulent eddies increases as the vertical motions are damped due to the stably stratified conditions. This effect is enhanced by the formation of a low-level jet after sunset. Finally, the comparison of the anisotropy ratio computed from the different sources of observations allow us to determine the most relevant scales of the motion during the AET in such a complex terrain region.